Recycling food waste to clean water: The use of a biodigester's residual liquid inoculum (RLI) to decolourise textile azo dyes - Maganha De Almeida, A. C. [UNESP]; Backhaus, J.; Corso, C. R. [UNESP] (IWA Publishing, 2018)
A residual liquid inoculum (RLI) was used to decolourise solutions of Acid Yellow 25 (AY25) and Direct Violet 51 (DV51) azo dyes. The RLI was obtained through anaerobic digestion of food waste from a university restaurant. The concentration of bacteria in the RLI was 8.45 × 107 CFU mL-1. Dye solutions (50 μg mL-1) were inoculated with the RLI (20% v/v) and incubated at room temperature. The decolourisation studies took place at microaerophilic and in-batch conditions and at pH = 2.50. Initially, the dyes were taken up from solution by biosorption; maximum colour removal was achieved after 3 hours of incubation, with 88.66% for AY25 and 77.65% of DV51. At prolonged incubation times (3-96 hours) decolourisation was mainly attributed to biodegradation of the azo solutions, with breakage of the azo bond, as detected by UV-VIS spectroscopy and Fourier transform infrared (FT-IR) analysis. Analysis of UV-VIS absorption rates of dyes showed, however, that AY25 was more readily biodegradable whereas DV51 was more recalcitrant to the action of the RLI.
Keywords: Acid Yellow 25; Anaerobic biodigester; Biodegradation; Biosorption; Direct Violet 51; Microbial consortium